CHANGES IN ABILITY OF SELF-DIRECTED LEARNING OF THE THIRD-YEAR STUDENTS ON PROBLEM-BASED LEARNING - Citra Insany Irgananda; Candra Sari Kurniawati; Triyoga Edwin Gautama; Septianita Incha A’raaf (Universitas Brawijaya, 2018)
Learning method applied in Faculty of Dentistry of Brawijaya University is Problem-based Learning (PBL). One of the purposes of PBL is to develop students’ ability of self-directed learning (SDL). SDL is students’ ability to learn independently. This ability is necessary to determine the need and objective of students’ learning. This research aims to compare the ability of SDL of the first-year students and the third-year students of undergraduate program in Faculty of Dentistry of Brawijaya University. This is pre-experimental research using one-group pretest-posttest design. Samples are divided into two groups. The first group is pre-test group consisting of students of 2014 that have ever joined PBL in their first year. Meanwhile, post-test group consists of students of 2014 that have ever joined PBL on their third year. Instrument used in this research is adapted questionnaires. Data is analyzed using Independent Samples T-test, resulting in significant difference of students’ SDL scores between the first year and the third year (p<0.05). The average SDL score of the first year is 228.85 while the third year is 218.20. It can be concluded from this research that students’ SDL score in the first year is higher than that in the third year, and both of them are significantly different.